PRODUKTIVITAS EKONOMI PEMANENAN HUTAN RAKYAT PADA BERBAGAI SORTIMEN KAYU - Gautama, Iswara; Budiaman, Budiaman; Muchtar, Andi Asikin; Sandalayuk, Marlinda (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study aims to determine the process of forests harvesting, forest harvesting and economic productivity of the people based on variations in the size of sortimen by PT. Nelly Jaya Pratama in District of Mengkendek, Tana Toraja Regency. The managers of public forests where specified Input and Output generated from forests harvesting. The experiment was conducted on July 29 to September 5, 2012, with research sites in the District of Mengkendek, Tana Toraja Regency. Data collection was performed by direct measurement in the field and on-site interviews research Lembang Buntu Datu, which is managed by PT. Nelly Jaya Pratama. The results revealed that the process of forests harvesting in District of Mengkendek, Tana Toraja Regency, consisting of felling, skidding, and transportation activities. Economic productivity gained by Industry (PT Nelly Jaya Pratama) is influenced by the size of the diameter and timber volume, but inversely related to income earned by the labor of harvesting.